A Campaign to Wear Masks in the Pesantren Community With a Counseling Approach - Arifin, Samsul; Ummah, Athik Hidayatul (Jurnal Ilmiah Peuradeun, 2021)
The Ministry of Health of the Republic of Indonesia held a national campaign movement to wear masks to prevent transmission of COVID-19. The movement was welcomed by the pesantren. The purpose of this study was to describe the movement of wearing masks with the at-tawazun counseling approach (pesantren-based counseling) in Pondok Pesantren Salafiyah Syafi'iyah Situbondo, East Java. This research used a service-learning approach. The results of this study revealed the campaign to wear masks by balancing (at-tawazun) between physical and spiritual efforts, namely: a counseling approach with (1) uswah hasanah techniques, namely giving concrete examples of wearing good masks, (2) megha' kalemmar aéngnga sé ta' lekkoa, namely modeling using masks from students figures so that they are imitated by other students, (3) mauidhah hasanah, namely educational speech using masks, (4) balance between targhib and ta'zir which is giving reinforcement or punishment, and (5) art, namely campaigns using masks through the students' art performance. This research should be adopted in several other pesantren or Islamic-based educational institutions for the campaign to wear masks. This research contributes to the development of "Islamic Guidance and Counseling", "Islamic Psychology", and several other counseling theories.